Achieved pregnancy with the delivery of a healthy child by TESE‐ICSI 7 years after bilateral adult orchidopexy: a case report. (10th October 2013) - Matsushita, K.; Yamaguchi, K.; Li, F.; Okada, K.; Ando, M.; Chiba, K.; Koshida, M.; Miyake, H.; Fujisawa, M.
Summary We report pregnancy with the delivery of a healthy child by TESE‐ICSI 7 years after bilateral adult orchidopexy. A 29‐year‐old patient presented with infertility and previous bilateral cryptorchidism, but no surgical treatment had ever been performed. His partner had been assessed by a gynaecologist, and no contributing female factors were detected. Orchidopexy and conventional testicular sperm extraction (TESE) were performed and microdissection TESE 10 months after orchidopexy. The second microdissection TESE with intracytoplasmic sperm injection (ICSI) was performed 7 years after orchidopexy. The couple achieved pregnancy with the delivery of a healthy child by TESE‐ICSI. It is concluded that bilateral orchidopexy in adulthood progresses spermatogenesis gradually, and microdissection TESE may succeed after a certain period of time following treatment.